Enhancing Discoverability: Transitioning a Board Game Collection from a LibGuide to a CollectionBuilder Site - Dong, Hanwen; Moreno, Perri; Rodrigues, Tyler; Stone, Julia (Information Technology and Libraries, 2025)
As board game collections continue to grow in popularity at academic institutions, the University of Idaho Library wanted to establish an accessible and easy-to-use discovery tool for its physical game collection. At the collections’ origins, a LibGuide was created by librarians for this purpose, but as the collection records continued to grow into the triple digits, something more adaptable and customizable was necessary. In the summer of 2023, a team of librarians came together to build a custom site to house the game collection’s information using CollectionBuilder, an open-source framework for digital collections and exhibits websites that are driven by metadata and powered by modern static web technology. Creating this site came with unique challenges and considerations specific to the University of Idaho Library’s needs in displaying their board games. CollectionBuilder’s ability to support iterative and agile development, ample instructional documentation, and seemingly endless customizations makes it a suitable solution for a growing and changing collection discovery tool.